Effect of ZnO nanoparticle sizes and illumination on growth inhibition of Escherichia coli and Staphylococcus aureus bacteria in cultivation medium. Issue 1 (January 2021) - Jíra, J; Rutherford, D; Mičová, J; Remeš, Z; Rezek, B
Abstract: We study antibacterial effects of the zinc oxide nanoparticles (ZnO NPs) in cultivation medium (Mueller-Hinton broth) on Gram-negative ( Escherichia coli ) and Gram-positive ( Staphylococcus aureus ) bacteria models. We compare synthesized ZnO hedgehog NPs and commercial ZnO NPs (50 nm and 20 μm nominal size) in different concentrations (1 mg/mL and 0.1 mg/mL). Results show that E. coli are more sensitive to the ZnO presence in the cultivation media than S. aureus . We also characterize influence of visible and UV light on the ZnO NP effects.